SARS-CoV-2 RNAs are processed into 22-nt vsRNAs in Vero cells - Liu, Yang; Rao, Jian; Mi, Yingjie; Chen, Lan; Feng, Lijuan; Li, Qi; Geng, Jianing; Yang, Xianguang; Zhan, Xiangjiang; Ren, Lili; Chen, Jinfeng; Zhang, Xiaoming (Frontiers in Immunology, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused the global pandemic, resulting in great fatalities around the world. Although the antiviral roles of RNA interference (RNAi) have been well studied in plants, nematodes and insects, the antiviral roles of RNAi in mammalians are still debating as RNAi effect is suspected to be suppressed by interferon (IFN) signaling pathways in most cell types. To determine the role of RNAi in mammalian resistance to SARS-CoV-2, we studied the profiling of host small RNAs and SARS-CoV-2 virus-derived small RNAs (vsRNAs) in the early infection stages of Vero cells, an IFN-deficient cell line. We found that host microRNAs (miRNAs) were dysregulated upon SARS-CoV-2 infection, resulting in downregulation of microRNAs playing antiviral functions and upregulation of microRNAs facilitating viral proliferations. Moreover, vsRNA peaked at 22 nt at negative strand but not the positive strand of SARS-CoV-2 and formed successive Dicer-spliced pattern at both strands. Similar characteristics of vsRNAs were observed in IFN-deficient cell lines infected with Sindbis and Zika viruses. Together, these findings indicate that host cell may deploy RNAi pathway to combat SARS-CoV-2 infection in IFN-deficient cells, informing the alternative antiviral strategies to be developed for patients or tissues with IFN deficiency.